Diagnosis of Marketing Orientation Reality for Service-Privating Hospital - Abdullah, Sami S. (Humanities Journal of University of Zakho, 2017)
This study aims to describing the reality of marketing Orientation in Private Hospital. Companies in regards of themes as (Customer Orientation, Competitor Orientation, Inter-functional coordination.) the sample has consisted of (62) forms that been distributed over the Private Hospital managers (directors) and (57) forms have receved. A descriptive methodology has been adopted accomplish the goals of the study. The questionnaire form has included two sections: the first section has been related to data and personal information, the second section has devoted for measuring marketing Orientation through having (17) provisions divided over (3) themes (axes). After conducting the study, the researcher has come up with a set of conclusions as following: The managers (directors) of Private Hospital have average level of recognition of marketing Orientation. There have been no differences of statistical indications (meanings) of managers’ responses in regards of marketing Orientation themes (topics) such as (Customer Orientation, Competitor Orientation, Inter-functional coordination.) With variation of (sex, age, …) The order of the marketing Orientation themes (Inter-functional coordination, Customer Orientation, Competitor Orientation, has been according to its availability or significance for the Private Hospital managers (directors).